2019
DOI: 10.1021/acs.jpcc.9b05409
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the Shock Initiation Threshold of 1,3,5-Triamino-2,4,6-trinitrobenzene (TATB) to Nuclear Quantum Effects

Abstract: Approximating the dynamics of atomic nuclei with classical equations of motion in molecular dynamics (MD) simulations causes an overprediction of the specific heat and omits zero-point energy which can have a significant effect on predictions of the response of materials under dynamical loading. We use quantum and classical thermostats in reactive MD simulations to characterize the effect of energy distribution on the initiation and decomposition of the explosive 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 75 publications
0
40
0
Order By: Relevance
“…For TATB, see Figure 1b, we used a simulation cell with 250 molecules (6000 atoms) in the triclinic crystalline lattice setting of Cady and Larson 45 . Atomic interactions were calculated using the ReaxFF-2018 46 parametrization that has previously been used to study the TATB system for shock loading and thermal decomposition 47,48 . Thermal decomposition under the presence of the external potential is simulated by linearly heating the system from 1000 K to 3000 K at various rates (from 4 K/ps to 40 K/ps) 49 .…”
Section: Many Body Distortions Of Tatbmentioning
confidence: 99%
“…For TATB, see Figure 1b, we used a simulation cell with 250 molecules (6000 atoms) in the triclinic crystalline lattice setting of Cady and Larson 45 . Atomic interactions were calculated using the ReaxFF-2018 46 parametrization that has previously been used to study the TATB system for shock loading and thermal decomposition 47,48 . Thermal decomposition under the presence of the external potential is simulated by linearly heating the system from 1000 K to 3000 K at various rates (from 4 K/ps to 40 K/ps) 49 .…”
Section: Many Body Distortions Of Tatbmentioning
confidence: 99%
“…Hamilton et al 64 Those authors found that including a quantum specific heat and zero-point energy in the dynamics contributes to an increase in apparent reactivity for a given shock pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Con rming the applicability of the force eld to the calculation system, is the basic work of molecular dynamics simulations. Many works were studied the applicability of the ReaxFF force eld to the HMX and other EMs, reporting that the force eld can well describe the equation of state of HMX [14] and the reaction process under different loading conditions [15][16][17][18][19] , but the applicability of the ReaxFF force eld to the mixed system composed of HMX and graphene has never been studied.…”
Section: Validation Of Reaxff-lg Force Eldmentioning
confidence: 99%
“…Understanding the role of Gr in mixture explosive is the based approach for reveal the decreasing sensitivity and complex detonation reactions. ReaxFF-lg molecular dynamics simulations (RMDS) [14] , which has been proposed by Liu et al, has been studied the reactions of HMX [15] , ICM-102 [16] , TATB [17] , CL-20 [18] , and CL-20/TNT. The ne results are compared with quantum mechanics calculations and experiments.…”
Section: Introductionmentioning
confidence: 99%